User´s satisfaction of community dental care in Reynosa, Tamaulipas - Morales-Reyes, Hilda Nelly; Martinez-Vidaurri, Carlos; Mayek-Pérez, Netzahualcoyotl (Horizonte Sanitario, 2023)
Objective: To evaluate the level of satisfaction in the care received by the users of the Dental Clinic of the Universidad México Americana del Norte (DC-UMAN) Allende.Material and method: The study was descriptive, observational, cross-sectional, and prospective. In 2019, an opinion survey on the structure, proceedings, and results of the care, as well as bio-demographics of each patient was applied to 200 patients selected by convenience sampling.Results: Patients aged between 21 and 60 years (71%), women (63%), married (45%), employees/housewives (57%) and a low frequency of concomitant diseases (10%) predominated. At an older age, there was a higher frequency of concomitant diseases (r=0.26; p